orsai, the Drosophila homolog of human ETFRF1, links lipid catabolism to growth control. - Fernandez-Acosta, M.; Romero, J.I.; Bernabó, G.; Velázquez-Campos, G.M.; Gonzalez, N.; Mares, M.L.; Werbajh, S.; Avendaño-Vázquez, L.A.; Rechberger, G.N.; Kühnlein, R.P.; Marino-Buslje, C.; Cantera, R.; et al. (BMC Biology, 2022)
Lipid homeostasis is an evolutionarily conserved process that is crucial for energy production, storage and consumption. Drosophila larvae feed continuously to achieve the roughly 200-fold increase in size and accumulate sufficient reserves to provide all energy and nutrients necessary for the development of the adult fly. The mechanisms controlling this metabolic program are poorly understood. Herein we identified a highly conserved gene, orsai (osi), as a key player in lipid metabolism in Drosophila. Lack of osi function in the larval fat body, the regulatory hub of lipid homeostasis, reduces lipid reserves and energy output, evidenced by decreased ATP production and increased ROS levels. Metabolic defects due to reduced Orsai (Osi) in time trigger defective food-seeking behavior and lethality. Further, we demonstrate that downregulation of Lipase 3, a fat body-specific lipase involved in lipid catabolism in response to starvation, rescues the reduced lipid droplet size associated with defective orsai. Finally, we show that osi-related phenotypes are rescued through the expression of its human ortholog ETFRF1/LYRm5, known to modulate the entry of ?-oxidation products into the electron transport chain; moreover, knocking down electron transport flavoproteins EtfQ0 and walrus/ETFA rescues osi-related phenotypes, further supporting this mode of action. These findings suggest that Osi may act in concert with the ETF complex to coordinate lipid homeostasis in the fat body in response to stage-specific demands, supporting cellular functions that in turn result in an adaptive behavioral response.